One-Pot CuO-Catalyzed Green Synthesis of N(N′)-Arylbenzamidines as Potential Enzyme Inhibitors - Taj, M.B.; Raheel, A.; Alelwani, W.; Babteen, N.; Kattan, S.; Alnajeebi, A.; Sharif, M.; Ahmad, R.H.; Abbas, -; Hazeeq, A.; Tirmizi, S.A.; Ali, Hapipah Mohd (Pleiades Publishing, 2019)
Ten N(N′)-arylbenzamidines were synthesized in 60–77% yield by one-pot microwave-assisted reaction of the corresponding N-arylbenzamides with aniline or ammonia in the presence of copper(II) oxide powder. The synthesized compounds were evaluated in vitro for inhibitory activity against several enzymes, namely acetylcholinesterase, butyrylcholinesterase, lipoxygenase, α-glucosidase, urease, and reverse transcriptase. Some compounds showed very good acetylcholinesterase and butyrylcholinesterase inhibitory activity. N′-(1,3-Benzothiazol-2-yl)- and N′-(1,3,4-thiadiazol-2-yl)benzamidines were the most active α-glucosidase inhibitors with IC50 values of 134.2 and 244.57 µM, respectively. N′-(1,3-Benzothiazol-2-yl)benzamidine also inhibited urease. Most of the obtained compounds showed inhibitory activity against reverse transcriptase (anti-HIV activity), presumably due to intermolecular hydrogen bonding, good solubility, and hydrophilicity. © 2019, Pleiades Publishing, Ltd.